Identification of maintainer and restorer lines in local aromatic Rice (Oryza sativa) (Bangladesh Journal of Agricultural Research, 2014)
The availability of stable cytoplasmic male sterility and fertility restoring system is vital for commercial exploitation of heterosis in rice. The experiment was conducted to identify stable maintainers and restorers for three CMS lines having wild abortive type sterility inducing genes in local rice germplasm. One hundred and twenty nine test crosses were made by using 43 aromatic rice genotypes and three CMS lines. Pollen sterility and spikelet fertility of the raised F1s were assessed in consecutive 2006-2007 Boro and 2007 T. Aman seasons. Pollen sterility was categorized as 100% sterility for complete sterile (CS), 91- 99% as sterile (S), 71-90% as partial sterile (PS), 31-70% as partial fertile (PF), 21-30% as fertile (F), and 0-20% sterility as full fertile (FF). Pollen sterility of F1s in Boro 2006-07 season ranged from 18.83 to 100%, while in T. Aman 2007 season, it ranged from 15.28 to 100%. Whereas spikelet fertility in Boro 2006- 07 season ranged from 0.86 to 69.71% and in T. Aman 2007 season, it ranged from 1.97 to 82.91% with CMS line IR58025A. Out of 43 F1s with IR58025A, two were found complete sterile (IR58025A/Kaliijira-9 and IR58025A/ Sorukamini-2) and three as full fertile (IR58025A/Agali, IR58025A/Benaful, and IR58025A/Khasa). With CMS line IR62829A, pollen sterility ranged from 2.77 to 100% in Boro 2006-07 season and 0.96 to 100% in T. Aman 2007 season. Spikelet fertility status of the same combinations ranged from 0 to 75.41% in Boro 2006-07 season and 1.76 to 88.36% in T. Aman season 2007. Six crosses were identified as complete sterile and seven as full fertile for the said combination. In case of IR68885A four crosses were found as complete sterile, and a single cross as full fertile. The local aromatic line, Kalijira-9 and Sorukamini were identified as maintainer for IR68885A which was common with IR58025A. The local aromatic line Benaful was identified as restorer for IR58025A and IR62829A. DOI: http://dx.doi.org/10.3329/bjar.v39i1.20056 Bangladesh J. Agril. Res. 39(1): 1-12, March 2014